Bonding Social Capital as a Milestone for Village-Owned Enterprises Existence (a Study of BUM Desa Kerjaya Krasa, Krocok Village, Japah District, Blora Regency) - Yonna Esty Kusuma; Suwarto Suwarto; Widiyanto Widiyanto (Publikasi Indonesia, 2022)
The Indonesian Government is currently trying to intensify the establishment and development of BUM Village to increase village income. The existence of BUM Village is expected to be a pillar of the village community’s economy, so that the existence of BUM Village needs to be maintained and further considered. The management of BUM Village is carried out by the village government together with the community, based on these reasons it is important to conduct further research on social processes related to the existence of bonding social capital in the development of BUM Village. One of the BUM Village that can maintain its existence is BUM Village Kerjaya Krasa, established in 2017. This paper aims to analyze the development and role of bonding social capital in BUM Village Kerjaya Krasa. The research was conducted qualitatively through in-depth interviews, observation, and documentation. The structural dimensions of social capital found are related to the good relationship between the BUM Village management, with the Krocok Villagers, and the Krocok Village Government. The cognitive dimensions of social capital that can be analyzed include written rules, norms, and sanctions. The relational dimensions that can be found are related to trust, transparency, reciprocity, and social values.